A Mechanistic Approach on the Cs2CO3 Mediated Synthesis of 4‐Azaindole Analogues Bearing Pyridine‐3‐Carboxamide and 1‐Phenylethanone. Issue 21 (2nd June 2022) - Atchuta Ramarao, T.; Jha, Anjali; Sen, Anik
Abstract: cesium carbonate mediated synthesis of desired 1 N‐substituted phenylethanone analogue of 4‐azaindole is carried out in Dimethylformamide. Further formation of derivatives of 6 is produced from desired analogue of 4‐azaindole. The mechanistic pathway is analyzed with density functional theory calculations which supported the experimental results. Due to structural similarity of azaindole core nucleus with purine ring of ATP, it is a promising /attractive molecule to be explored for its biological potential. Abstract : A base catalyzed room temperature synthesis of 4‐azaindole analogue followed by different derivatives which can be promising as potential biological molecules have been synthesized followed by Density functional theory mediated mechanistic studies.